Analisis HPP Metode Full Costing: Dari Skenario Markup Harga Jual Menuju Pencapaian Target Laba Bersih UMKM Soto Bogor Slipi: HPP Analysis of Full Costing Method: From the Selling Price Markup Scenario Towards the Achievement of the Net Profit Target of MSMEs Soto Bogor Slipi - Zahidah Cahya Handayani; Nabilla Dzuhriana Azzahroh; Sallsa Billa Dini Azzahra; Diandra Riski Andini; Nadia Selvirana Herman (PT Cakrawarti Empat Proksi, 2026)
This research is motivated by the importance of accurately determining the cost of production (HPP) for Micro, Small, and Medium Enterprises (MSMEs), especially in the culinary sector. The need for accurate calculation of the Cost of Production (COG) for MSME producers is an important factor in determining selling prices and operating profits. Many MSMEs continue to use simple cost calculations, so that the price set is not able to generate the best profit. The purpose of this study is to test the use of the full-cost method in determining the cost of production and the impact of the selling price setting scenario on the achievement of the net profit target of Soto Bogor Slipi MSMEs. This research method uses a descriptive quantitative approach with a case study on Soto Bogor Slipi MSMEs. The object of the study focused on the production and sales data of Soto Bogor Slipi MSMEs during the research period. The analysis technique was applied using the HPP calculation of the full costing method. The findings of the study show that the total production cost according to the calculation results of Soto Bogor Slipi MSMEs is Rp. 11,441,970 for 400 portions with a cost of production (HPP) of Rp. 29,000 per portion, while the calculation using the full costing method results in a total production cost of Rp. 12,111,970 with an HPP of Rp. 31,000 per portion. There is a difference of Rp. 2,000 caused by the method used by MSMEs that have not included all cost components in full, especially variable factory overhead costs. The results of the analysis also show that the business has reached a break-even point in the sale of at least 305 portions with the actual number of 400 portions and obtained a net profit of Rp. 858,000 with a profit margin of 6.5%. The implementation of this scenario can achieve the net profit target with the right selling price markup and Soto Bogor Slipi MSMEs can achieve optimal results. It is hoped that this study will have an impact in creating a successful and sustainable pricing strategy.